Naldemedine Effective at Relieving Opioid-Induced Constipation - Hoyle, Brian (MD Conference Express, 2015)
A phase 2b randomized, double-blind, placebo-controlled study shows that naldemedine, a peripherally acting µ-opioid receptor antagonist, is effective in easing opioid-induced constipation compared to placebo. Phase 3 development is expected for the 0.2 mg/day naldemedine dose.